Semantic Analysis of the Expressions Interpretation of Bliss Throughout Romantic Context in Taylor Swift’s Songs - Syahid, Agus; Wulandari, Alivia Oktaviona; Sudewi, Ni Ketut Putri Nila (Humanitatis : Journal of Language and Literature, 2024)
Semantic analysis through the study of contextual meaning theory is a useful approach to examine the meaning of song lyrics in detail. This approach allows us to delve further into the layers of meaning implied behind the series of words contained in the lyrics to reveal aspects that may not be explicitly visible but are at the core of the communication between the songwriter and his audience. This research aims to provide a deeper understanding of concepts such as happiness represented and communicated through poetic language in Taylor Swift’s songs. The research method used is a descriptive qualitative method of relevant song lyrics and cognitive semantic studies used in analyzing data sourced from several Taylor Swift songs. The results of this study show that Taylor Swift uses conceptual metaphors and figurative meanings to describe happiness in love relationships. In the song "Lover," Taylor Swift uses metaphors of travel and freedom to express happiness in living their relationship. In "Call It What You Want," she uses light and endurance metaphors to convey the happiness gained from lasting love. In "Sweet Nothing," Swift uses the metaphor of physical manifestation to describe happiness in simple moments.